On Constraining the Mesoscale Eddy Energy Dissipation Time‐Scale. (23rd November 2022) - Mak, J.; Avdis, A.; David, T.; Lee, H. S.; Na, Y.; Wang, Y.; Yan, F. E.
Abstract: A physically plausible lower bound on the spatially varying geostrophic mesoscale eddy energy dissipation time‐scale within the ocean, related to the geographical energy transfer rate out of the geostrophic mesoscales, is provided by means of a simple and computational inexpensive inverse calculation. Data diagnosed from a high resolution global configuration ocean simulation is supplied to a parameterized model of the geostrophic mesoscale eddy energy, from which the dissipation time‐scale results as a solution to an optimization calculation. We find that the dissipation time‐scale is shortest in the Southern Ocean, in the Western Boundary Currents, and on the western boundaries, consistent with the expectation that these regions are notable sites of baroclinic activity with processes leading to energy transfer out of the geostrophic mesoscales. Although our solution should be interpreted as a lower bound given the assumptions going into the calculation, it serves as an important physically consistent base line reference for further investigations into ocean energetics, as well as for an intended inference calculation that is more complete but also much more complex. Plain Language Summary: Energy plays an important role in quantifying the magnitude of motions at different time and spatial scales. Many different dynamical processes contribute to energy transfers within the ocean, and constraining the rate of transfer remains a formidable challenge. This work provides a bulk constraint on the overall magnitude and spatial variation of an eddy energy dissipation time‐scale, which relates to the rate of energy transfer out of the motions at 10–100 km in the ocean where rotation and density stratification play a leading order role in the dynamics. A time‐scale is "backed out" from a model via an inverse approach: given a model for the eddy energy evolution and what we should end up with (the eddy energy signature), what should we have started off with in the first place (the dissipation time‐scale)? Although our solution should be interpreted as a lower estimate given the assumptions going into the calculation, it serves as an important physically consistent base line reference for further investigations into ocean energetics, as well as for an intended inverse calculation that is more complete but also much more complex. Key Points: Constraining the mesoscale eddy energy dissipation time‐scale in the ocean via a simple and computationally inexpensive inverse calculation Shortest dissipation time‐scale in Southern Ocean, Western Boundary Currents, and ocean western boundaries Computes a spatially varying lower bound dissipation time‐scale to guide future investigations